An integrated 200-W class-D audio amplifier. - Berkhout, M. (IEEE Journal of solid state circuits)
An integrated stereo class-D audio power amplifier realized in a silicon-on-insulator (SOI)-based BCD technology is presented. The amplifier is capable of delivering 2×100 W in two 4-Ω loads at a supply voltage of 60 V. A second-order feedback loop is used to suppress supply ripple and pulse-shape errors in the switching power stage. The limiting factor in the performance of any class-D amplifiers is the quality of the switching power stage. A high-speed low-current levelshifter and a robust deadtime control arrangement are proposed that enable the realization of a robust high-quality switching power stage. Some practical issues with respect to robustness and electromagnetic compatibility are discussed.